Village Head Leadership in Increasing Community Participation in Mendik Makmur Village, Longkali District, Paser Regency - Bela Rismayana; Anwar Alaydrus (Jurnal Ilmu Pemerintahan, 2021)
The purpose of this study was to find out and analyze the personality characteristics of the village head who is able to provide motivation and input to the community so that there is community participation in Mendik Makmur Village, Longkali District, Paser Regency. This study uses leadership indicators, namely initiative, motivation, coaching, and responsibility as well as to determine the supporting and inhibiting factors in increasing community participation. The data analysis technique used is an interactive model data analysis technique. The results of the study show that in general the leadership of the Mendik Makmur Village Head has carried out its obligations well and always invites the community to participate in village development activities. Then, the village head gave initiatives in the form of suggestions so that the community always innovates to increase productivity, then the motivation given was in the form of encouraging sentences, namely by saying the jargon "Together We Can" in each activity, there was direct coaching from the village head who spent more time with the community, the form of responsibility is in the form of budget transparency, timeliness in distributing aid and the Village Head gives trust to his community to always be creative in their respective fields. With the encouragement of a community leader who has a passion for change and the spirit of mutual cooperation that is starting to emerge, it becomes a supporting factor that is very influential in increasing community participation. Then the community has also started trying to make changes due to direct awareness from the Village Head. While the inhibiting factors for community participation are constraints on work schedules, and differences in political choices.